High-entropy alloy particle reinforced copper-based contact material and preparation method and application thereof

By adding high-entropy alloy particles to the copper-based contact material, using ball milling and plasma hot pressing sintering, the performance shortcomings of existing CuCr alloy contacts were solved, and Cu-HEAs contact materials with excellent mechanical properties and arc corrosion resistance were prepared.

CN119685645AActive Publication Date: 2025-03-25YUNNAN POWER GRID CO LTD

Patent Information

Application Number
CN202411873555.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing CuCr alloy contacts have shortcomings in terms of breaking capacity, interception level, corrosion resistance and welding resistance, and are difficult to meet the needs of high-performance electrical contact materials.

Method used

The preparation method of high-entropy alloy particles reinforced copper-based contact material is adopted. By weighing the alloy powder, the HEAs powder is obtained, and then mixed with the copper powder for secondary ball milling and plasma hot pressing sintering to prepare Cu-HEAs composite powder.

Benefits of technology

The prepared Cu-HEAs contact material has excellent mechanical properties, arc corrosion resistance and voltage resistance, which significantly improves the overall performance of copper-based contact material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685645A_ABST
    Figure CN119685645A_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy alloy particle reinforced copper-based contact material and a preparation method and application thereof, and belongs to the technical field of contact materials. The reinforced-phase high-entropy particles are added into the copper matrix to improve the ablation resistance of the contact material. Powder of five different elements is mixed, subjected to ball milling and annealed to obtain high-entropy alloy powder, then copper powder and the high-entropy powder are mixed and subjected to ball milling to obtain Cu-HEAs composite powder, and finally the high-entropy alloy reinforced copper-based contact material is obtained through the SPS hot pressing sintering technology. The Cu-HEAs contact material has excellent physical and mechanical properties, the arc erosion resistance of the copper-based contact material is enhanced, and the service life of a contact is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of contact materials, and in particular relates to a high entropy alloy particle reinforced copper-based contact material and a preparation method and application thereof. Background Art

[0002] Electrical contact materials are important components of electrical systems and are mainly used in switches, relays and circuit breakers. CuCr alloys are widely used in vacuum circuit breakers due to their high voltage resistance, large breaking current capability, good resistance to welding and low current cut-off performance. However, CuCr contacts have some shortcomings in breaking capacity, current cut-off level, corrosion resistance and welding resistance, and it is imperative to develop contact materials with excellent comprehensive performance.

[0003] In recent years, high entropy alloys (HEAs) have attracted more and more attention due to their unique composition and microstructure. HEAs have high strength, high hardness and good high temperature stability. At the same time, the lattice distortion effect of HEAs will increase the degree of electron scattering during the power-on process, and the binding energy and work function will also increase. Therefore, high entropy alloys have good resistance to arc erosion and anti-welding properties.

[0004] This patent adds HEAs to copper-based contacts to study the breaking capacity, interception level, arc erosion resistance and welding resistance of Cu-HEAs, and analyzes the role of HEAs in them. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a high entropy alloy particle reinforced copper-based contact material.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions, including:

[0009] The alloy powders are weighed separately, degreased and dried, mixed, ball-milled, and annealed to obtain HEAs powders;

[0010] Weighing Cu powder, degreasing it, washing it and drying it, then mixing the Cu powder and HEAs powder and performing secondary ball milling to obtain Cu-HEAs composite powder;

[0011] Plasma hot pressing and sintering of Cu-HEAs composite powder under vacuum conditions; after the sintering, a high entropy alloy reinforced copper-based contact material is obtained;

[0012] The Cu-HEAs composite powder includes 80-95 wt. % of Cu powder and 5-20 wt. % of HEAs powder.

[0013] As a preferred embodiment of the method for preparing the high entropy alloy particle reinforced copper-based contact material of the present invention, the alloy includes one or more of Co, Cr, Fe, Ni, Cu, Mn, and Al.

[0014] As a preferred solution of the method for preparing the high entropy alloy particle reinforced copper-based contact material of the present invention, the particle size of the alloy powder is 30 to 60 μm.

[0015] As a preferred solution of the method for preparing the high entropy alloy particle reinforced copper-based contact material of the present invention, the alloy powder is mixed in an equiatomic ratio.

[0016] As a preferred scheme for the preparation method of the high entropy alloy particle reinforced copper-based contact material described in the present invention, the first ball milling uses zirconium oxide grinding balls, the ball-to-material ratio is 10 to 20:1, the ball milling medium is anhydrous ethanol, the ball milling speed is 500 to 1000 rpm, and the ball milling time is 0 to 30 hours.

[0017] As a preferred embodiment of the method for preparing the high entropy alloy particle reinforced copper-based contact material of the present invention, the annealing step comprises: the annealing temperature is 400 to 600° C. and the annealing time is 1 to 3 hours.

[0018] As a preferred embodiment of the method for preparing the high entropy alloy particle reinforced copper-based contact material of the present invention, the high-energy ball milling has a ball milling speed of 100 to 300 rpm and a ball milling time of 0 to 3 hours.

[0019] As a preferred scheme for the preparation method of the high-entropy alloy particle reinforced copper-based contact material described in the present invention, the process parameters of the plasma hot pressing sintering are: a sintering temperature of 700-900°C, a sintering pressure of 2.2-4.2MPa, a heating rate of 20-50°C / min, and a sintering time of 0.5-1.5h; the drying temperature is 40-60°C.

[0020] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a high entropy alloy particle reinforced copper-based contact material.

[0021] The purpose of the present invention is to overcome the deficiencies in the prior art and provide an application of a high entropy alloy particle reinforced copper-based contact material in the preparation of a high-voltage switch.

[0022] Beneficial effects of the present invention:

[0023] The present invention adopts high-energy ball milling to prepare HEAs powder with a dual-phase structure and mixes it with copper powder evenly, and then uses spark plasma sintering technology to prepare a new type of Cu-HEAs contact material with a uniform and compact microstructure, and HEAs particles are evenly dispersed in the copper matrix. The new contact Cu-HEAs has excellent mechanical properties, arc erosion resistance and voltage resistance, and provides a new idea for preparing copper-based contact materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:

[0025] Figure 1 It is a simplified flow chart of the preparation method of the present invention.

[0026] Figure 2 This is a scanning electron microscope image of the contact material prepared in Example 1. DETAILED DESCRIPTION

[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0029] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0030] The raw materials used in the present invention are all commercially available unless otherwise specified.

[0031] The performance of the material prepared in the embodiment of the present invention was tested as follows:

[0032] The density of the contact was measured using a density tester (MH-300G, Shanghai Shuju Instrument Technology Co., Ltd.) using the Archimedean principle. The conductivity of the contact was measured using an eddy current conductivity meter (FD-102, Xiamen Foster Electronic Technology Co., Ltd.). The hardness of the sample was measured using a Vickers hardness tester (MH-3, Jitai Scientific Instruments) at room temperature, where the applied load was 100g and the loading time was 3s. The contact alloy before and after arc erosion was weighed using an electronic balance (ME204E, METTLERTOLEDO, Switzerland) to calculate its mass change.

[0033] Example 1

[0034] This embodiment provides a method for preparing a high entropy alloy particle reinforced copper-based contact material. Figure 1 , specifically:

[0035] (1) Preparation of high entropy alloy (HEAs) powder

[0036] 2.14 g Cu powder, 2.13 g Co powder, 2.13 g Ni powder, 1.72 g Cr powder and 1.88 g Fe powder were weighed, with a particle size of 30 to 60 μm, and degreased respectively, and then washed with anhydrous ethanol and deionized water, and then dried at 50° C. under vacuum conditions; the powders were mixed and placed in a ball mill, and zirconium oxide balls were added, and the ball-to-material ratio was controlled to be 15:1, 1.5 g anhydrous ethanol was added, and the ball mill speed was set to 900 rpm, and the ball milling time was 24 h. The ball-milled powder was annealed in a tube furnace, and the temperature was set to 500° C. for 2 h to obtain HEAs powder;

[0037] (2) Preparation of Cu-HEAs composite powder

[0038] 8.5 g of Cu powder and 1.5 g of HEAs powder were weighed, the Cu powder was degreased, then washed with anhydrous ethanol and deionized water, and then dried at 50° C. under vacuum conditions; the Cu powder and the HEAs powder were mixed, placed in a ball mill for high-energy ball milling, the ball milling speed was set to 200 rpm, the ball milling time was 0.5 h, and ball milling was performed to obtain a Cu-HEAs composite powder;

[0039] (3) Preparation of high entropy alloy reinforced copper-based contact materials

[0040] The Cu-HEAs composite powder is placed in a graphite mold with a diameter of 20 mm, and then the graphite mold is placed in a plasma hot pressing sintering furnace. The vacuum is drawn and the sintering process is set. The sintering pressure is set to 3.2 MPa, the sintering temperature is set to 800°C, the heating rate is set to 35°C / min, and the sintering time is set to 1 h. After the end, a high entropy alloy reinforced copper-based contact material is obtained.

[0041] Figure 2 This is a scanning electron microscope image of the contact material prepared in this embodiment. It can be seen that the microstructure of the Cu-HEAs contact material is uniform and compact, and the HEAs particles are uniformly dispersed in the copper matrix.

[0042] The sample prepared in this embodiment has a relative density of 90.7%, a conductivity of 34.2% IACS, and a hardness of 72.3 HV, which fully meets the technical requirements.

[0043] Example 2

[0044] The difference between this embodiment and embodiment 1 is that the sintering pressure is adjusted from 3.2 MPa to 2.2 MPa, and the rest of the preparation process is the same as that of embodiment 1, to obtain a high entropy alloy particle reinforced copper-based contact material.

[0045] Example 3

[0046] The difference between this embodiment and embodiment 1 is that the sintering pressure is adjusted from 3.2 MPa to 4.2 MPa, and the rest of the preparation process is the same as that of embodiment 1, to obtain a high entropy alloy particle reinforced copper-based contact material.

[0047] Comparative Example 1

[0048] The difference between this comparative example and Example 1 is that the sintering pressure is adjusted from 3.2 MPa to 1.2 MPa, and the rest of the preparation process is the same as that of Example 1, to obtain a high entropy alloy particle reinforced copper-based contact material.

[0049] During the sintering process, due to the low sintering pressure, a porous structure exists inside the sample, and a uniform and dense sample cannot be obtained, which affects the performance of the sample.

[0050] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 1.

[0051] Table 1

[0052] Relative density Electrical conductivity hardness Mass loss after arc erosion Example 1 90.7% 34.2%IACS 72.3HV 0.05mg Example 2 86.3% 30.4%IACS 60.7HV 0.11mg Example 3 90.1% 33.1%IACS 71.3HV 0.08mg Comparative Example 1 79.9% 23.1%IACS 57.5HV 0.17mg

[0053] As can be seen from the above table, adjusting the sintering pressure has a significant effect on the performance of the copper-based contact material. This is because during the sintering process, the sintering pressure promotes the rearrangement of particles, reduces the number and size of pores, and obtains a more uniform and dense structure. Insufficient pressure may lead to a porous structure, while excessive pressure may cause particle deformation. The size and number of pores directly affect the hardness and conductivity of the material. According to the results in the above table, the best technical effect can be obtained when the sintering pressure in the present invention is 3.2MPa.

[0054] Example 4

[0055] The difference between this embodiment and embodiment 1 is that the sintering temperature is adjusted from 800° C. to 700° C., and the rest of the preparation process is the same as that of embodiment 1, to obtain a high entropy alloy particle reinforced copper-based contact material.

[0056] Example 5

[0057] The difference between this embodiment and embodiment 1 is that the sintering temperature is adjusted from 800° C. to 900° C., and the rest of the preparation process is the same as that of embodiment 1, to obtain a high entropy alloy particle reinforced copper-based contact material.

[0058] Comparative Example 2

[0059] The difference between this comparative example and Example 1 is that the sintering temperature is adjusted from 800° C. to 1000° C., and the rest of the preparation process is the same as that of Example 1, to obtain a high entropy alloy particle reinforced copper-based contact material.

[0060] During the sintering process, the high sintering temperature leads to rapid grain growth and increased defects, which affects the performance of the sample.

[0061] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 2.

[0062] Table 2

[0063]

[0064]

[0065] It can be seen from the above table that adjusting the sintering temperature has a significant effect on the performance of the copper-based contact material, because the sintering temperature can affect the porosity, particle bonding degree and microstructure of the material, thereby affecting the basic physical properties of the material. According to the results in the above table, the best technical effect can be obtained when the sintering temperature in the present invention is 800°C.

[0066] Example 6

[0067] The difference between this embodiment and embodiment 1 is that the heating rate is adjusted from 35°C / min to 25°C / min, and the rest of the preparation process is the same as that of embodiment 1 to obtain a high entropy alloy particle reinforced copper-based contact material.

[0068] Example 7

[0069] The difference between this embodiment and embodiment 1 is that the heating rate is adjusted from 35°C / min to 45°C / min, and the rest of the preparation process is the same as that of embodiment 1 to obtain a high entropy alloy particle reinforced copper-based contact material.

[0070] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 3.

[0071] Table 3

[0072] Relative density Electrical conductivity hardness Mass loss after arc erosion Example 1 90.7% 34.2%IACS 72.3HV 0.05mg Example 6 90.1% 32.7%IACS 71.6HV 0.08mg Example 7 90.5% 33.4%IACS 72.1HV 0.06mg

[0073] It can be seen from the above table that adjusting the heating rate has a significant effect on the performance of the copper-based contact material, because the heating rate can affect the microstructure and grain growth of the material, and thus have an important impact on the density, hardness and conductivity. According to the results in the above table, the best technical effect can be obtained when the heating rate in the present invention is 35°C / min.

[0074] Example 8

[0075] The difference between this embodiment and embodiment 1 is that the sintering time of 1h is adjusted to 0.5h, and the rest of the preparation process is the same as that of embodiment 1, and a high entropy alloy particle reinforced copper-based contact material is obtained.

[0076] Example 9

[0077] The difference between this embodiment and embodiment 1 is that the sintering time is adjusted from 1h to 1.5h, and the rest of the preparation process is the same as that of embodiment 1, to obtain a high entropy alloy particle reinforced copper-based contact material.

[0078] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 4.

[0079] Table 4

[0080] Relative density Electrical conductivity hardness Mass loss after arc erosion Example 1 90.7% 34.2%IACS 72.3HV 0.05mg Example 8 90.3% 33.1%IACS 71.9HV 0.07mg Example 9 90.6% 33.8%IACS 72.1HV 0.06mg

[0081] As can be seen from the table above, adjusting the sintering time has a significant effect on the performance of the copper-based contact material, because the sintering time can affect the density, grain growth and microstructure of the material, thereby affecting the hardness and conductivity. According to the results in the table above, the best technical effect can be obtained when the sintering time in the present invention is 1h.

[0082] Comparative Example 3

[0083] The difference between this comparative example and Example 1 is that the reinforcement phase is adjusted to Al, Co, Ni, Cr and Fe powders, and the rest of the preparation process is the same as that of Example 1 to prepare Cu-AlCoNiCrFe HEAs contact alloy.

[0084] The prepared Cu-AlCoNiCrFe HEAs contact alloy has a relative density of 90.9%, a hardness of 71.5 HV, a conductivity of 33.1% IACS, and a mass loss of 0.13 mg after arc erosion. Compared with the Cu-HEAs contact alloy prepared in Example 1, the various properties are not much different, but after arc erosion, the various properties decrease rapidly.

[0085] In summary, the present invention adopts high-energy ball milling to prepare HEAs powder with a dual-phase structure and mixes it with copper powder evenly, and then uses spark plasma sintering technology to prepare a new type of Cu-HEAs contact material with a uniform and compact microstructure, and HEAs particles are evenly dispersed in the copper matrix. The new contact Cu-HEAs has excellent mechanical properties, arc erosion resistance and withstand voltage strength, providing a new idea for the preparation of copper-based contact materials.

[0086] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a high entropy alloy particle reinforced copper-based contact material, characterized in that: include, The alloy powders are weighed separately, degreased and dried, mixed, ball-milled, and annealed to obtain HEAs powders; Weighing Cu powder, degreasing it, washing it and drying it, then mixing the Cu powder and HEAs powder and performing high-energy ball milling to obtain Cu-HEAs composite powder; Plasma hot pressing and sintering of Cu-HEAs composite powder under vacuum conditions; after the sintering, a high entropy alloy reinforced copper-based contact material is obtained; The Cu-HEAs composite powder includes 80-95 wt. % of Cu powder and 5-20 wt. % of HEAs powder.

2. The method for preparing a high entropy alloy particle reinforced copper-based contact material according to claim 1, characterized in that: The alloy includes one or more of Co, Cr, Fe, Ni, Cu, Mn, and Al.

3. The method for preparing a high entropy alloy particle reinforced copper-based contact material according to claim 1, characterized in that: The particle size of the alloy powder is 30 to 60 μm.

4. The method for preparing a high entropy alloy particle reinforced copper-based contact material according to claim 1, characterized in that: The alloy powders are mixed in equal atomic ratios.

5. The method for preparing a high entropy alloy particle reinforced copper-based contact material according to claim 1, characterized in that: The primary ball milling uses zirconium oxide grinding balls, a ball-to-material ratio of 10 to 20:1, anhydrous ethanol as the ball milling medium, a ball milling speed of 500 to 1000 rpm, and a ball milling time of 0 to 30 hours.

6. The method for preparing a high entropy alloy particle reinforced copper-based contact material according to claim 1, characterized in that: The annealing process has an annealing temperature of 400 to 600° C. and an annealing time of 1 to 3 hours.

7. The method for preparing a high entropy alloy particle reinforced copper-based contact material according to claim 1, characterized in that: The high-energy ball mill has a ball milling speed of 100 to 300 rpm and a ball milling time of 0 to 3 hours.

8. The method for preparing a high entropy alloy particle reinforced copper-based contact material according to claim 1, characterized in that: The process parameters of the plasma hot pressing sintering are: sintering temperature of 700-900°C, sintering pressure of 2.2-4.2MPa, heating rate of 20-50°C / min, sintering time of 0.5-1.5h; the drying temperature is 40-60°C.

9. The high entropy alloy particle reinforced copper-based contact material prepared by the preparation method according to claims 1 to 8.

10. Use of the high entropy alloy particle reinforced copper-based contact material according to claim 9 in the preparation of a high-voltage switch.

Citation Information

Patent Citations

  • High-performance metal-matrix composite preparation method

    CN104911379A

  • Preparation method of CoCrCuFeMoNi high-entropy alloy particle reinforced copper base composite material

    CN108220642A

  • Preparation method of high-melting-point high-entropy magnetically soft alloy

    CN113073250A

  • Method for manufacturing high-entropy alloy reinforced copper-based composite material, product and application

    CN115351296A

  • High-strength high-thermal-conductivity high-entropy alloy particle reinforced copper-based composite material and preparation method thereof

    CN118996181A

Cited By

  • WMoTaNb-Cu composite material and preparation method thereof

    CN121065562A

  • A wmo tanb-cu composite material and a method for manufacturing the same

    CN121065562B